Where does price discovery occur in FX markets? - Chris D'Souza (Bank of Canada, 2007)
Trades in foreign exchange markets are initiated around the world and around the clock. This study illustrates that trades are more informative when initiated in a local country or in major foreign exchange centers like London and New York. Evidence suggests that informational asymmetries based on geography arise from the market making capacity of dealers and the customer order flow that dealers capture during regional business hours. Findings also show that market orders initiated in price-correlated FX markets are not informative. Transparency in quotes on electronic trading platforms may prevent informed participants from exploiting information across FX markets. Overall, these results are robust across different market conditions.
Keywords: F31; G15; 330; Market structure and pricing; Exchange rates; Financial markets; Devisenhandel; Devisenmarkt; Wechselkurs; Asymmetrische Information; Welt